Increased serum levels of fibroblast growth factor 23 after an ultradistance run. Issue 3 (March 2021) - Kerschan-Schindl, Katharina; Skenderi, Katerina; Wahl-Figlash, Katharina; Gelles, Katharina; Föger-Samwald, Urusla; Thalmann, Markus; Tsironi, Maria; Szekeres, Thoms; Pietschmann, Peter
Abstract: Objectives: Healthy bones need to be loaded on a regular basis. However, overstrenuous exercise causes uncoupling of bone metabolism. Thus, it is important to be aware of exercise-induced alterations in bone metabolism. The aim of this observational study was to determine whether participation in an ultradistance run has an impact on the phosphaturic hormone fibroblast growth factor 23 (FGF23), which is produced by osteocytes and suppresses osteoblast differentiation as well as matix mineralization. Design: Observational study. Methods: Nine participants of the Spartathlon (246 km) had venous blood samples taken before and within 15 min after finishing the race as well as during recovery. Serum levels of FGF23, phosphate, and blood urea nitrogen were determined. Results: FGF23 increased 6.5-fold from pre-race to post-race (2.2 pmol/L [IQR: 0.4; 3.2 pmol/L] to 14.4 pmol/L [IQR: 4.7; 20.0 pmol/L]; p = 0.001). Thereafter, serum levels of FGF23 fell to 1.4 pmol/L [IQR: 0.5; 1.7 pmol/L] (p < 0.0001). The differences in FGF23 levels between pre-race and recovery (3 days after the start) did not achieve statistical significance (p = 0.614). Serum levels of phosphate and blood urea nitrogen also did not change significantly. Conclusions: Since FGF23 plays a central role in mineral homeostasis, the transient overexpression of FGF23 may be an important contributor to the short-term uncoupling of bone metabolism induced by overstrenuous exercise.